Teachers Performance and Satisfaction of Medical School : How The Role of Knowledge Sharing, and Organizational Citizenship Behaviour (OCB) ? - Khiong, Khie (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this study was to analyze the relationship of knowledge sharing variables to medical teachers performance, the relationship of knowledge sharing variables to medical teachers satisfaction, the relationship of organizational citizenship behavior (OCB) variables to medical teachers performance, the relationship of organizational citizenship behavior (OCB) variables to medical teachers satisfaction. This research method is quantitative through a survey by distributing online questionnaires to 200 medical school teachers who were selected by simple random sampling method. Data analysis using structural equation modeling (SEM) with data processing tools is SmartPLS 3.0 software. Stages of data analysis is to test the validity, reliability, coefficient of termination and hypothesis testing. The results of this study indicate that the variable knowledge sharing has a positive and significant effect on medical teachers performance, the variable knowledge sharing has a positive and significant effect on medical teachers satisfaction, the variable organizational citizenship behavior (OCB) has a positive and significant effect on medical teachers performance, and organizational variables. citizenship behavior (OCB) has not significant effect on medical teachers satisfaction. The novelty of this research is a new model of knowledge sharing and organizational citizenship behavior (OCB) variables on teachers performance and teachers satisfaction.